PELATIHAN KOMPETENSI KURIKULUM UJI KOMPETENSI KEAHLIAN (UKK) UNTUK MENINGKATKAN KEMAMPUAN PADA ASPEK SOFT SKILL DI SMK TRIGUNA - Damanik, Hillman Akhyar; Anggraeni, Merry; Faisal, Farid Abdi (Jurnal Abdi Insani, 2024)
One of the government program of competency improvement is the assurance of education quality, especially for vocational high school students. One of them is the Uji Kompetensi dan Keahlian (UKK) which aims to assess the improvement of educational qualifications. The implementation of UKK at SMK Triguna still has obstacles for students in its implementation practices, especially the imbalance between theory and practice and students' readiness to do practical. To overcome these existing constrains, the PKM proposal team conducted activities in the form of workshops and implementation of UKK practical to help design and provide practical experience for students. The implementation of workshops and implementation of UKK, was designed according to the qualifications of the students, by designing and configuring the UKK packet 1 program, namely Designing Network Security, Installation and Configuration of Dynamic Routing, (2) Designing Cable and Wireless Based Networks with VLAN and Routing techniques. The results of the PKM activities carried out obtained scientific achievements of 40% for the conceptual and implementation of packet 1 material and 45% for conceptual understanding and implementation of UKK packet 2. The output of the implementation of this PKM activity, the proposing team will also create a configuration template for the implemented Router device, training material modules and grants for MikroTik RB951 router hardware equipment and switches for UKK packet 1 and packet 2 questions and assignments. From the results of the implementation of the PKM workshop and practical, it shows an increase from each student of 40% for Package 1 and 45% for Package 2 in the UKK program.